Модифікований метод автоматизації прийняття управлінських рішень для створення команди управління проектами - Чорна, О.В.; Люшенко, Л.А.; Рибачок, Н.А. (Управляющие системы и машины, 2019)
Запропоновано модифікацію «наївного» байєсівського алгоритму з використанням байєсівської мережі для автоматизації прийняття управлінських рішень, а саме для автоматизованого підбору команди проекту. Модифікація методу полягає у використанні обмеження на структуру графа, де кожен вузол додатково може мати не більше одного з батьків серед інших вхідних змінних. Застосування модифікованого методу надає кращий результат за критеріями точності та швидкодії у підборі учасників команди. Целью данного исследования является разработка модифицированного метода автоматизации процесса принятия решений на основе интеллектуального анализа данных. Методы. Используя эту модификацию, будет достигнута лучшая точность при оценке выбора каждого члена команды с учетом большого количества входных параметров, которые описывают профессиональные навыки и компетенции работников. Результаты. Для анализа эффективности предложенного способа модификации было реализовано соответствующее программное обеспечение с использованием языка C #. Для сравнения был также реализован алгоритм Наивного Байеса в Matlab. Тестирование проводилось с использованием различных дел. Модифицированный метод автоматизации процесса принятия решений по выбору проектной команды показал лучшие результаты по критериям точности, чем стандартный метод MatLab, а также более высокую производительность. Purpose. The purpose of this research is to develop a modified method of automation decision-making management process based on data mining. Methods. Modification of the method consists in using the restriction on the structure of the graph and considering such an extension of the Naive Bayes classifier, where each node can additionally have no more than one parent among other input variables. Using this modification, better accuracy will be achieved in assessing the selection of each team member, taking into account a large number of input parameters that describe the professional skills and competencies of the workers. Results. To analyze the effectiveness of the proposed method modification, appropriate software was implemented using C# language. There was also implemented Naive Bayes algorithm in Matlab for comparison. Testing was carried out using a variety of personal cases. The modified method of automation decision-making management process of choosing a project team showed better results for accuracy criteria than the standard MatLab method, as well as a higher per-formance.